Turning into Gods: Transhumanist Insight on Tomorrow's Religiosity - Masson, Olivier (Implicit religion, 2014)
Transhumanism has been a part of modern culture since the early years of the twentieth century. Since Julian Huxley, (brother of the famous writer Aldous Huxley), first used the term in 1957 to describe what he called a "new belief " in the capability of the human species to "transcend itself," transhumanism has been going through a continuous institutionalization process. After spending the second half of the twentieth century as a major leitmotiv of science fiction, since the dawn of the new millennium a large number of texts dealing with the creation of a new human species have been published as non-fiction: thus, what was considered a few years ago to be genuine science fiction themes, are now presented as non-fiction. However much this crossover from fictional to non-fictional may have changed the face of transhumanism, it has nevertheless left intact its narrative dimension. In this article we argue that this narrative is what gives transhumanism its implicit religious dimension.